(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Acute myocardial infarction (MI) is one of the leading causes of mortality and morbidity associated with cardiovascular diseases. Left ventricular thrombous (LVT) is one of the important complications of myocardial infarction. LVT significantly increases the morbidity and mortality associated with MI. The embolic complications of LVT include stroke, vital organs infarct and limb ischemia. In this study we tried to find out the frequency of LVT in our population at 48 hours and at 1 week after acute MI. This would help us in better understanding of this potential life threatening complication of MI in our population. Objective: The objective of the study is to determine the frequency of left ventricular thrombus after acute anterior wall myocardial infarction at 48 hours after MI and at 1week in those patients that didn’t have LV thrombus at initial assessment at 48hours. Study Design: It was a descriptive case series. Setting: The Study was conducted in CCU, cardiology department Jinnah Hospital Lahore. Sample Selection: All patients of both genders with age range of 25-85 years, of acute anterior wall STelevation myocardial infarction (excluding old infarct patients, patients already having thrombus, contraindications to thrombolytic therapy) from May 2013 to Sep 2013 were selected. Results: LVT was seen in 25 patients (19.2%) out of the total 130 patients included in the study. LVT was seen in 7 (5.4%) patients at 48 hours and 18 new cases of LVT (13.8% of total 130 patients and 14.63% of 123 patients without LVT at 48 hours) were seen at 1 week. Conclusion: The overall frequency of LVT after acute MI was 19.2%. More number of patients with LVT was diagnosed at 1 week than at 48 hours. If LVT is not seen in patients after acute anterior wall MI at 48 hours, then repeat echocardiography at 1 week can be helpful in diagnosing this life threatening complication of acute MI among high risk patients.